Translation as growth: Xiangsheng’s growing trajectory in China and abroad - Ye Tian; Guanpeng Wang (JoSTrans: The Journal of Specialised Translation)
To survive in different environments, performances adapt and grow to the measure of the different conditions of reception offered by these contexts. This article reviews the development in China and abroad of xiangsheng, or ‘crosstalk’, a Chinese comic double-act that relies on quickfire exchanges and narrative skills on stage. It brings together a blend of scripted material and improvisation whose address to the audience is immediate. Through the ecological metaphors of growth and using the lens of semiotic translation, we characterise translation as growth and explore the complexities in xiangsheng’s developing trajectories over time. We review xiangsheng’s development in China by examining current archives and research and examine its growth in diasporic performers by combining interviews with semiotic and textual analysis. Our exploration reveals that translation enables the intermingling of political tension, performers’ self-awareness, audiences’ social and cultural background, and the broader historical background of the form itself as it grows and evolves in different times and locations.